Product-Oriented Environmental Management Systems (POEMS) 2013
DOI: 10.1007/978-94-007-6116-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment for the Agri-Food Sector

Abstract: DIAS reports primarily contain research results and trial statements aimed at Danish conditions. Also, the reports describe larger completed research projects or acts as an appendix at meetings and conferences. DIAS reports are published in the series: Plant production, Animal Husbandry and Horticulture. ContentsPreface 7Life cycle assessment of bread production -a comparison of eight different scenarios -9Braschkat, J., Patyk, A., Quirin, M., & Reinhardt, G. A. 9 When a hole matters -the story of the hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
(42 reference statements)
0
5
1
Order By: Relevance
“…The significant contribution of the transport item was also reported by Kendall et al [21], who established that the Carbon Footprint of honey was in a range from 0.4 to 1.4 kg CO 2 e/kg of honey while also considering the pollination services. The CF results obtained by using economic-value-based allocation in order to include pollination services were generally lower than those found in our assessment [8,[21][22][23]. The differences in the values reported in LCA studies indicated that honey's CF is strongly dependent on the method applied, as well as on the production practices and honey beekeeping chain characteristics [22].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The significant contribution of the transport item was also reported by Kendall et al [21], who established that the Carbon Footprint of honey was in a range from 0.4 to 1.4 kg CO 2 e/kg of honey while also considering the pollination services. The CF results obtained by using economic-value-based allocation in order to include pollination services were generally lower than those found in our assessment [8,[21][22][23]. The differences in the values reported in LCA studies indicated that honey's CF is strongly dependent on the method applied, as well as on the production practices and honey beekeeping chain characteristics [22].…”
Section: Discussioncontrasting
confidence: 77%
“…In particular, LCA studies focused on sugar estimated a variable Carbon Footprint range from 0.45 to 6.31 kg CO 2 e/kg of sugar depending on the technologies applied and the type of cultivation [6,7]. However, in the literature, there have been only a few LCAs implemented in apiculture [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the application of LCA to agro-food productions, several studies are available in the literature [26][27][28]; in particular, research in fruit sector has assumed a growing relevance starting from 2005. Concerning the wine sector, in the last decade there was an increasing interest in LCA applications, underlining the great relevance that the environmental issues play also in this sector [29,30].…”
Section: Methodological Backgroundmentioning
confidence: 99%
“…Splitting the life cycle of wine into five sub-systems (farming, transformation, packaging, distribution and use), it has been found that the agricultural phase represents the most important potential source of greenhouse gas emissions, due to the consumption of fossil fuels for mechanical operations [30][31][32]. Comparative assessment is one of principal types of application performed by international scholars.…”
Section: Methodological Backgroundmentioning
confidence: 99%
“…In general, LCA provides a reliable and complete quantification of net environmental impacts, thus providing alternatives to decision and policy makers [12,13]. This method is widely applied in the agricultural sector [14][15][16][17][18][19][20][21][22] and, in particular, in the viticulture and vinification sectors [23,24]. In this connection, LCA allows the environmental performance of the overall wine sector to be investigated [25], mainly through the "cradle-to-grave" approach, i.e., considering the grape production, vinification, bottling, and distribution [26].…”
Section: Introductionmentioning
confidence: 99%